1996
DOI: 10.1210/jcem.81.5.8626847
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I (IGF-I) and IGF-binding proteins in children with nephrotic syndrome.

Abstract: Growth failure appears to be a major problem for nephrotic children who fail to respond to steroid therapy. Recently altered serum insulin-like growth factor (IGF) and IGF-binding protein (IGFBP) profiles are reported in renal failure and glomerulonephritis. In this study, the serum IGFBP profile was evaluated by Western ligand blot and RIA in 22 patients with the nephrotic syndrome. Serum IGFBP-3 was decreased, whereas IGFBP-2 was increased in most patients with the nephrotic syndrome. The mean serum IGFBP-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…IGFs were mainly excreted in the urine in the 45-kD molecular weight form, but IGFs in the 150-kD form also appeared in the urine of some nephrotics [38]. Similar results have been reported in nephrotic children [39]. In a recent study reported by Haffner et al [40], in nephrotic children, the serum immunoreactive IGFBP-3 levels were found to be elevated due to an increase in the low molecular weight IGFBP fragments, while there was a decrease in the 150-kD IGFBP ternary complex in the serum with an excess of low molecular weight IGFBPs.…”
Section: The Igf-igfbp System In the Nephrotic Syndromesupporting
confidence: 77%
“…IGFs were mainly excreted in the urine in the 45-kD molecular weight form, but IGFs in the 150-kD form also appeared in the urine of some nephrotics [38]. Similar results have been reported in nephrotic children [39]. In a recent study reported by Haffner et al [40], in nephrotic children, the serum immunoreactive IGFBP-3 levels were found to be elevated due to an increase in the low molecular weight IGFBP fragments, while there was a decrease in the 150-kD IGFBP ternary complex in the serum with an excess of low molecular weight IGFBPs.…”
Section: The Igf-igfbp System In the Nephrotic Syndromesupporting
confidence: 77%
“…Nevertheless, we cannot exclude a systemic disturbance of the growth hormone/IGF-1 axis, as increased renal excretion and reduced circulating levels of IGF-1 and IGFbinding proteins have been reported in the NS. 31,32 This disturbance might contribute to growth and development retardation described both in experimental models and in children with poorly controlled NS. 5,33 We did not observe growth retardation, as estimated by tibial length, in PANtreated rats.…”
Section: Discussionmentioning
confidence: 99%